Mechanism of Evolution of Koneramine Complexes from One‐Pot Reactions: Snapshots of Intermediates Offer Facile Routes to New Dipicolylamines. Issue 11 (9th May 2018) - Raje, Sakthi; Mondivagu, Nandakishor; Chahal, Manoj; Butcher, Ray J.; Angamuthu, Raja
Abstract: Koneramines (L R OR′, R=Ph or Ts; R′=Me, i Pr) and their complexes were found to emerge from the system of pyridine‐2‐carboxaldehyde and N ‐phenyl/tosylethylenediamine when a primary or secondary alcohol was used as solvent. Imidazolidinylpyridines (L R, R=Ph or Ts) became major emergents whereas hemi‐aminals (L R OH, R=Ph or Ts) are minor emergents of the system when tertiary butanol was used as the solvent; the bulky tertiary butyl group prevented the addition of alcohol to the iminium ion that diverted the equilibrium towards imidazolidinylpyridines. By playing with the components of the reaction mixture, crystals of the metastable intermediates bound to copper(II) and/or zinc(II) were obtained and the structures were determined by X‐ray diffraction analysis. The reported results shed light on how to control the emergents of the multicomponent reaction mixture that forms koneramines. Reactivity studies of the intermediates pave the way for a new type of koneramine complexes that are new dipicolylamines where the two pyridine moieties of the resulting koneramine are not the same. Abstract : Follow and find them : By controlling the components of the system that yielded koneramine, the hypothesized metastable intermediates, such as imidazolidinylpyridine and hemi‐aminal precursor of koneramine, were isolated in coordinated form and studied. Isolation of the imidazolidinylpyridine–metal complex offers a simple synthetic route for new forms of koneramines with mixed pyridine donors.